2014
DOI: 10.1111/jce.12426
|View full text |Cite
|
Sign up to set email alerts
|

Atrioesophageal Fistula Complicating Cryoballoon Pulmonary Vein Isolation for Paroxysmal Atrial Fibrillation

Abstract: Although atrioesophageal fistula (AEF) formation is a well known, albeit rare, catastrophic complication of atrial fibrillation radiofrequency ablation procedures, there are less data regarding this complication using the cryoballoon technique. We report on 3 cases of AEF as a complication of cryoballoon pulmonary vein isolation at 3 different institutions with 2 different generations of cryoballoons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 13 publications
1
41
1
Order By: Relevance
“…12 As of today, 5 cases of AEF after CB-PVI have been described in the literature: 3 cases with the CB1 9,10 and 2 cases with the CB2. 8,9 During all reported cases, continuous LET measurement was not, or could not, be performed because of temperature probe design or malfunction. [8][9][10] Systematic postprocedural esophagoscopy results after CB-PVI have been reported in 3 studies using the CB1 [13][14][15] and 2 studies using the CB2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 As of today, 5 cases of AEF after CB-PVI have been described in the literature: 3 cases with the CB1 9,10 and 2 cases with the CB2. 8,9 During all reported cases, continuous LET measurement was not, or could not, be performed because of temperature probe design or malfunction. [8][9][10] Systematic postprocedural esophagoscopy results after CB-PVI have been reported in 3 studies using the CB1 [13][14][15] and 2 studies using the CB2.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 During all reported cases, continuous LET measurement was not, or could not, be performed because of temperature probe design or malfunction. [8][9][10] Systematic postprocedural esophagoscopy results after CB-PVI have been reported in 3 studies using the CB1 [13][14][15] and 2 studies using the CB2. 11,16 Collectively, these studies reported esophageal ulcerations in 6 of 116 (5.2%) and 11 of 82 (13.4%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esophageal injury is sometimes seen in radiofrequency- and cryo-ablation and results from collateral injury to the esophagus while ablating in the left atrium (LA). Such esophageal injury is due to the close physical proximity of the esophagus in relation to the posterior wall of the LA[4, 5]. One strategy for avoiding this complication is to not ablate in areas in the LA that are in contact with the esophagus[6, 7]; however, it is difficult to identify the esophageal location during the ablation procedure.…”
Section: Introductionmentioning
confidence: 99%
“…A conformational study 50 showed that the disruption of the myelin sheath and Schwann cell elements occurs, but nerves regenerate to normal functioning Q23 within 2 weeks of ablation. Damage to nerves occurs as a gradient based on temperature.…”
Section: Q22mentioning
confidence: 99%